EDUKASI HUKUM BISNIS DI ERA DIGITAL: MEMBANGUN KESADARAN LEGALITAS DAN KEPASTIAN HUKUM BAGI PELAKU USAHA - Rizqi, Aditya Maulana; Gusti, Nabila Secioria Ciptaning (ICON Publisher, 2025)
The purpose of this community service activity is to enhance business legal literacy among students of Universitas Muhammadiyah Gombong and young entrepreneurs, enabling them to understand and apply the principles of legality in digital business practices. The implementation method utilizes an experiential learning approach through workshops, electronic contract simulations, and relevant local case studies within the context of digital enterprises. Participants receive interactive learning on business law aspects, digital contracts, as well as compliance with regulations and personal data protection. The effectiveness of the activity is evaluated through pre-tests and post-tests, accompanied by participant feedback to measure the increase in legal knowledge and awareness. The results show a significant improvement in legal understanding, with the average post-test score rising from 58.6 to 79.0. These findings affirm that experiential learning methods can enhance legal literacy and build sustainable regulatory awareness among the younger generation amid the dynamics of digital business.